Mammalian life depends on two distinct pathways of DNA damage tolerance - Buoninfante, Olimpia Alessandra; Pilzecker, Bas; Spanjaard, Aldo; de Groot, Daniël; Prekovic, Stefan; Song, Ji-Ying; Lieftink, Cor; Ayidah, Matilda; Pritchard, Colin E J; Vivié, Judith; Mcgrath, Kathleen E; Huijbers, Ivo J; et al. (Proceedings of the National Academy of Sciences - PNAS, 2023)
DNA damage threatens genomic integrity and instigates stem cell failure. To bypass genotoxic lesions during replication, cells employ DNA damage tolerance (DDT), which is regulated via PCNA ubiquitination and REV1. DDT is conserved in all domains of life, yet its relevance in mammals remains unclear. Here, we show that inactivation of both PCNA-ubiquitination and REV1 results in embryonic and adult lethality, and the accumulation of DNA damage in hematopoietic stem and progenitor cells (HSPCs) that ultimately resulted in their depletion. Our results reveal the crucial relevance of DDT in the maintenance of stem cell compartments and mammalian life in unperturbed conditions.